Rare complication of milk-alkali ingestion: severe pancreatitis and acute kidney injury in a chronic hypocalcaemic patient with DiGeorge's syndrome. Issue 3 (15th March 2019) - Bhadra, Rajarshi; Khan, Fareeha Ahmed; Soliman, Mona; Somasundaram, Meyappan; Iltchev, Daniel V; Ravakhah, Keyvan
Abstract : Injudicious use of over-the-counter calcium supplements has resulted in increased incidences of hypercalcaemia and related complications. We present a case of acute pancreatitis in a chronic hypocalcaemic patient of DiGeorge's syndrome. The patient came into the ED with sepsis syndrome, right upper quadrant and epigastric pain and no obvious source of infection. Lab results and imaging were indicative of acute pancreatitis. There was severe renal dysfunction. The patient needed haemodialysis and had a prolonged stay in intensive care. The medical history was negative for biliary duct pathology or alcohol use. The patient had vomiting and diarrhoea in the nursing home for about a week, but she continued to receive her regular medications that included the calcium supplements and thiazide diuretics. It is likely that a complex interplay between calcium supplementation, dehydration and thiazide diuretics resulted in the development of acute pancreatitis and severe renal dysfunction in a chronic hypocalcaemic patient.